Vivre centenaire et bien portant : Pour une longévité réussie - Georget-Tessier, Dominique (Essentiel : l'encyclopédie d'Utovie., 2016)
Vast field of successful longevity, important issue at a time when, if life expectancy increases, that of living in good health decreases. Wide reflection, as if thinking about his longevity implies being attentive to his body, it also involves s occupy the mind. The author presents here the conditions necessary to live healthy centenary: a careful diet, physical exercises adapted of course, but also an active social engagement, open spirituality, great sex and assumed ... It also presents the contributions of medicines traditional Greek, Chinese, Indian in this search for balance. And also encourages s inspire lifestyle centenary of the island of Okinawa, Japan. Georget-Dominique Tessier is a general practitioner, she practiced for 30 years near Pau. It practices integrative medicine articulating the biomedical knowledge in homeopathy, acupuncture, micronutrition the phytoaromathérapie, psychosomatic medicine. She is one of the leaders of the BASIC Association (Béarn Food Health Environment). She has published in the same collection: Cancer and diet.